Industry 4.0 Readiness - DBS Bank Singapore Case Study - Soeung, Hong (2020)
The thesis will focus on the concept of the Industry 4.0, the importance of human capital and competencies in corporation to become ready for the industrial revolution.Methodology will be based on secondary data analysis on annual reports, published statistics and other sources, along with a case study of a well-renowned company (DBS Bank Singapore), which successfully transformed to a smart company.